CHARACTERISTICS OF UPPER THIRD MOLAR IMPACTION IN BANDUNG CITY POPULATION - Alifya Fahira; Indra Hadikrishna; Lucky Riawan; Yurika Ambar Lita (Odonto : Dental Journal, 2022)
Background: The third molars (M3) are the most frequently impacted teeth because they are the last to erupt, so they often don’t get enough space to erupt. The characteristics of impacted M3 teeth can be different for each person. This study aims to provide a description of maxillary M3 impaction based on age, sex, classification, treatment, and anesthesia in Bandung City population. Method: This was a descriptive study using secondary data from medical records and panoramic radiographs at RSGM UNPAD with a purposive sampling technique. Determination of the characteristic impaction using a classification based on Archer, Shiller, Jung and Cho, and Killy and Kay, analyzed with ImageJ software by interobserver and intraobserver, and tested using Kappa statistics for reliability.Result: There were 134 impacted teeth from 102 impacted patients with 67 females (66.34%) and most cases occurred in 17-25 years old (60.4%); Class B, 82 cases (60.9%); distoangular angulation, 76 cases (56.72%); Class 3, 76 cases (52.24%); and one fused roots, 83 cases (64.93%). The most common procedure performed was odontectomy (87.25%) with local anesthesia (63.73%)Conclusion: Characteristics of upper M3 impaction in terms of position, angulation, and its relation to age and sex is needed for the diagnosis, so the management plan by the clinician is better and safer. Panoramic radiography can still be used to determine classification and diagnosis in preparing a treatment plan even though it has limitations.